Alfven wave instability based on temperature anisotropy with non-maxwellian distribution function - Qureshi, M.N.S.; Saeed, Sundas; Shah, H.A. (Вопросы атомной науки и техники, 2013)
Space observations by numerous satellites reveal that the distributions often possess non-Maxwellian characteristics such as high energy tails or flat top (broad shoulders) in the profile of distribution functions. Distributions with high energy tails are well modelled by family of kappa type distribution. However, when distributions contain flat tops with or without high energy particles, generalized (r,q) distribution function is the best choice. In general the spectral index r corresponds to the flat part of the distribution and q to the high energy tail in the profile of the distribution function. By following the kinetic theory, we employ this distribution function to study the Alfven waves in anisotropic plasma and found that Alfven wave can grow when there is temperature anisotropy in plasma. Instability conditions are then studied for different temperature ratios by using the plasma parameters observed downstream the bow shock by CLUSTER. Космические наблюдения многочисленных спутников показывают, что немаксвелловские распределения часто обладают такими характеристиками, как высокие энергетические хвосты или плоские вершины (широкие плечи) в профиле функций распределения. Распределения с высокими энергетическими хвостами хорошо моделируются семейством распределений типа каппа. Однако, когда распределения содержат плоские вершины с или без высокоэнергетических частиц, тогда лучшим выбором является обобщенная (r,q)-функция распределения. В общем, спектральный индекс r соответствует плоской части распределения, а q соответствует высокому энергетическому хвосту в профиле функции распределения. Следуя кинетической теории, мы использовали эту функцию распределения для изучения альфвеновских волн в анизотропной плазме и обнаружили, что альфвеновская волна может расти при наличии температурной анизотропии в плазме. Условия неустойчивостей затем изучались при различных соотношениях температуры, используя параметры плазмы, которые наблюдались вниз по потоку ударной волны в CLUSTER. Космічні спостереження чисельних супутників показують, що немаксвеллівські розподілення часто володіють такими характеристиками, як високі енергетичні хвости або плоскі вершини (широкі плечі) в профілі функцій розподілу. Розподіл з високими енергетичними хвостами добре моделюється сімейством розподілів типу каппа. Однак, коли розподіл містить плоскі вершини з або без високоенергетичних часток, тоді кращим вибором є узагальнена (r, q)-функція розподілу. Загалом, спектральний індексr відповідає плоскій частині розподілу, а q – високому енергетичному хвосту в профілі функції розподілу. Відповідно до кінетичної теорії, ми використовували цю функцію розподілу для вивчення альфвенівських хвиль в анізотропній плазмі і виявили, що альфвенівська хвиля може рости при наявності температурної анізотропії в плазмі. Умови нестійкостей потім вивчалися при різних співвідношеннях температури, використовуючи параметри плазми, які спостерігалися вниз по потоку ударної хвилі в CLUSTER.